Integration of Seismic Facies and Seismic Sequence analysis for Depositional Environment Reconstruction of nandy Field, Niger Delta - Atueyi, Ifeyinwa Obiageli; Ayolabi, Elijah Adebowale; Okpogo, Emele Uduma; Abbey, Chukwuemeka Patrick (Iraqi Journal of Science, 2018)
An integrated seismic sequence stratigraphy and facies analysis has been carried out with a view to understanding the depositional environment and stratal stacking pattern of Nandy Field of Niger Delta. Well logs and biostratigraphic information were used to identify the lithologies, stratal stacking patterns, stratigraphic surfaces, system tracts and reservoir potentials of the field. Seismic sequence stratigraphy and seismic reflection patterns were used to identify the seismic facies. Facies-related attributes were employed to identify the continuity and amplitude of seismic events. Three seismic facies packages and three reservoir sands were identified. The environments of deposition of the area consist of marginal marine to continental depositional settings predominantly made of shoreface deposits with few channel sands. The depositional model of the area shows that the deposition went down the axis of fluvial depositional system, which transports sediments through channels down to the shelf into the base of the slope down the basin. The seismic reflection patterns in this field are parallel to divergent reflections, high-continuity and high-amplitude facies, low-amplitude facies, low-continuity and variable-amplitude reflections, chaotic reflections and wavy reflection patterns. The seismic stratigraphic analysis of this field revealed the presence of low stand system tract (LST), high stand system tract (HST) and transgressive system tract (TST). Sands 1 and 2 were delineated within high stand systems tract (HST) while sand 3 was within low stand systems tract (LST). The results of this study show that the Nandy Field was of high hydrocarbon potentials and highlight the importance of using seismic reflection parameters (reflection configuration, amplitude, frequency and continuity) in the division and classification of seismic facies.